A prelude to the molecular systematics and diversity of combtooth blennies (Teleostei: Blenniidae) in the Persian Gulf and Oman Sea. Issue 5 (4th July 2021) - Mehraban, Hamidreza; Zarei, Fatah; Esmaeili, Hamid Reza
Abstract : Despite being labelled as impoverished, with low species richness for many taxonomic groups, beta diversity of the northern marginal waters of the Indian Ocean is found to be high. To facilitate future investigation of near-shore marine fish diversity in this region, we established a COI reference database for intertidal combtooth blennies (Blenniidae) and document the results of the first molecular taxonomic inventory of this group along the northern coasts of the Persian Gulf and Oman Sea. A combined use of various molecular species delimitations, phylogenetic and phylogeographic analyses was employed on a final library including this local database and archived sequences to define phylogenetic relationships and species boundaries, and to compare the results to the existing morphology-based taxonomy. The absence of reciprocal monophyly between two species, Istiblennius lineatus and I. pox, and the presence of deep phylogeographic breaks in another two widely distributed species, Antennablennius bifilum and Omobranchus punctatus was documented, indicating the potential existence of hidden taxonomic diversity in both taxa. Distinct phylogeographic patterns were discovered between different species of blenniid within the Persian Gulf and Oman Sea, which are discussed in reference to regional paleoclimate and life history. Establishment of this local database for the blenniids of the Persian Gulf and Oman Sea not only can serve as a reliable database for accurate specimen identification, but also is highly relevant to conservation programs, further taxonomic works and advanced evolutionary analyses on the blenniids of the Indo-Pacific.